2001
DOI: 10.1152/ajpcell.2001.281.6.c1978
|View full text |Cite
|
Sign up to set email alerts
|

Role of JNK in hypertonic activation of Cl-dependent Na+/H+ exchange in Xenopus oocytes

Abstract: In the course of studying the hypertonicity-activated ion transporters in Xenopus oocytes, we found that activation of endogenous oocyte Na(+)/H(+) exchange activity (xoNHE) by hypertonic shrinkage required Cl(-), with an EC(50) for bath [Cl(-)] of approximately 3mM. This requirement for chloride was not supported by several nonhalide anions and was not shared by xoNHE activated by acid loading. Hypertonicity-activated xoNHE exhibited an unusual rank order of inhibitory potency among amiloride derivatives and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…In this study, we also tested SP600125, a widely used JNK inhibitor in cell-based assays (4,14,32), to inhibit JNK activation and the subsequent regulation of cytokine production. We found that SP600125 had a potent inhibitory effect on JNK phosphorylation; however, it also inhibited rHagB-induced ERK phosphorylation, at least at concentrations greater than 1 M, and had a suppressive effect on the production of all the tested cytokines at concentrations higher than 1 M (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also tested SP600125, a widely used JNK inhibitor in cell-based assays (4,14,32), to inhibit JNK activation and the subsequent regulation of cytokine production. We found that SP600125 had a potent inhibitory effect on JNK phosphorylation; however, it also inhibited rHagB-induced ERK phosphorylation, at least at concentrations greater than 1 M, and had a suppressive effect on the production of all the tested cytokines at concentrations higher than 1 M (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Specific JNK inhibitors [16][17][18][19], CC0209766, CC0223105, and CC-401 were synthesized by Signal Pharmaceuticals, Inc. Each JNK inhibitor is dissolved in vehicle before injection (5% 1-methyl-2-pyrrolidone, 30% PEG-400, 25% PEG-200, 20% propylene glycol, USP, 20% 0.9% sodium chloride for injection, USP). JNK inhibitors (3-20 mg/kg rat, dissolved in 0.6-8.0 mg/ml vehicle) or equivalent volume of vehicle only are administrated intravenously at 15 min before starting ischemia.…”
Section: Reagentsmentioning
confidence: 99%
“…MAPKs have been implicated in shrinkageinduced NHE1 activation in some cell types [20,21], yet not in others [22]. Interestingly, recent studies have assigned a role for NHE1 upstream of activation of ERK1/2 after exposure to angiotensin II or 5-HT [23], as well as after cardiomyocyte stretch [24].…”
Section: Introductionmentioning
confidence: 99%